Donor tissue culture conditions and outcome after descemet membrane endothelial keratoplasty - Laaser, Kathrin; Bachmann, Bjoern O.; Horn, Folkert; Schlötzer-Schrehardt, Ursula; Cursiefen, Claus; Kruse, Friedrich (American Journal of Ophthalmology, 2011)
To investigate the effect of culture conditions of donor tissue on functional outcome after Descemet membrane endothelial keratoplasty.Retrospective, single-center, consecutive case series.Descemet membrane endothelial keratoplasty was performed routinely in 82 eyes of 82 consecutive patients using corneal donor tissue prestored in either short-term culture (Optisol-GS; Bausch & Lomb) at 4 C (group A; n = 37) or organ culture (Dulbecco Modified Eagle Medium [Biochrom]; CorneaMax Medium [Eurobio]) at 34 C (group B; n = 45) in a randomized fashion. Main outcome measures included the number of air injections necessary for graft attachment as well as best-corrected visual acuity (in logarithm of the minimal angle of resolution [logMAR] units), central corneal thickness, and endothelial cell density at 1, 3, and 6 months after surgery.Best-corrected visual acuity increased from 0.69 ± 0.53 logMAR and 0.67 ± 0.31 logMAR before surgery to 0.33 ± 0.21 logMAR and 0.28 ± 0.18 logMAR after 1 month (P < .05), to 0.24 ± 0.16 logMAR and 0.18 ± 0.16 logMAR after 3 months (P < .05), and to 0.18 ± 0.12 logMAR and 0.15 ± 0.10 logMAR after 6 months (n.s.) in groups A and B, respectively. Endothelial cell density decreased from 2647 ± 236 cells/mm(2) and 2515 ± 249 cells/mm(2) before surgery to 1499 ± 277 cells/mm(2) and 1526 ± 205 cells/mm(2) after 1 month (P < .05), to 1441 ± 213 cells/mm(2) and 1443 ± 316 cells/mm(2) after 3 months (n.s.), and to 1587 ± 366 cells/mm(2) and 1457 ± 285 cells/mm(2) after 6 months (n.s.) in groups A and B, respectively. Central corneal thickness declined from 664 ± 89 and 662 ± 107 ?m before surgery to 529 ± 92 ?m and 517 ± 62 ?m after 1 month (P < .05), to 511 ± 46 ?m and 510 ± 46 ?m after 3 months (P < .05), and to 529 ± 68 ?m and 507 ± 50 ?m after 6 months (n.s.) in groups A and B, respectively. Best-corrected visual acuity, endothelial cell density, and central corneal thickness values showed no significant differences between both groups at any time point after surgery. However, a significantly higher total number of air injections was necessary in group A (n = 34) compared with group B (n = 26) to obtain graft attachment (P < .05).These findings suggest that donor tissue culture conditions have no significant effect on functional outcome, but may influence graft adhesion and rebubbling rate after Descemet membrane endothelial keratoplasty surgery.
EVALuna2:21002